Semmelweis: una rilettura - Del Missier, Giovanni; Monducci, Elena (Il sogno della farfalla, 2005)
The article examines the life and work of the famous Hungarian obstetrician Ignàc Semmelweis, who discovered the prophylaxis of puerperal fever in 1847. The Author discusses the wide range of literature available on the subject starting from the recent edition of S. B. Nulands’, The doctor’s plague. Germs, childbed fever and the strange story of Ignàc Semmelweis (New York 2003) that re-examines with great vigour the human and scientific vicissitudes of Semmelweis. The Author then offers a comparison between the tragic story of Semmelweis whose discoveries earned him harsh opposition from the academic institutions leading him to suicide, with that of the lives of other protagonists with similar stories but different outcomes. Taking a critical look at the thesis of Nuland, which highlights the responsibilities and the errors of Semmelweiss himself, the Author points out that whilst, on the one hand, he was able to achieve a positive practical result Semmelweis was not able to base it on an exact scientific theory. This shortcoming could explain the reasons for his defeat in that cultural milieu.